Effect of Heat Leakage on Relativistic Quantum Lenoir Engine Performance with a Massless Boson as Working Substance in the Infinite Potential Box - Saputra, Yohanes Dwi; Rahastama, Swastya; Firdaus, Rohim Aminullah (POSITRON, 2024)
A study on the effect of heat leakage on power output, thermal efficiency, and reversibility rate in a relativistic quantum Lenoir engine has been conducted. Initially, we analogize the quantum working substance of the engine, a massless boson trapped in an infinite potential box with a movable right wall, as an ideal gas confined in a pistoned cylinder. Then, the total work, heat input, and heat output of each engine cycle which consists of isochoric, adiabatic expansion, and isobaric compression are extracted by applying the concept of quantum thermodynamics. Finally, power output, thermal efficiency, and reversibility rate of the engine are calculated for different variations of the heat leakage constant. The results are the relationship between several parameters which are expressed in the graph of thermal efficiency vs. compression ratio, graph of efficiency/normal efficiency vs. compression ratio, power output vs. efficiency, and reversibility rate vs. compression ratio. The conclusion is that an increase in heat leakage has an effect on reducing the efficiency and reversibility rate of the engine but does not affect its power output. This work will provide a new chapter for further research related to the use of the boson particle as a working substance in the quantum heat engine, especially the study of the heat leakage effect on engine performance.